Children of the Earth. No.9 (Midsummer, 1983) - (:unkn) unknown (Children of the Earth, 1983)
As You Can See … -- Changes -- Transmission Problems / by Morag na Bienne, Church of Seven Arrows -- Book Reviews: McGuffey's Eclectic Readers / review by Linda ; Ride the River by Louis L'Amour / recommendation by Linda and Hestia ; Woman Chief / recommended by Hestia ; The Fairies' Alphabet Book / recommended by Clytemnestra -- Wanted: Solutions for Mundane Household Problems -- Notes From the Broom Closet: So What Can I Teach My Kids? / by Could -- Make Believe / poem by Filisis -- The Placenta: A Link Between Two Worlds / by Robin -- Reader Survey -- Conception / Robin
1 Electronic record(s). 3936022 bytes. 8 pages. CotE_v03n09_1983.pdf
Keywords: Children of the Earth (Newsletter); Neopagan families; Child rearing--Religious aspects--Neopaganism; Child rearing--Religious aspects--Wicca; Robins--Poetry; Make believe--Poetry; Placenta--Religious aspects; Conception--Poetry; Poetry; Reviews; Reader surveys; Newsletters